How does autoimmune disease impact treatment and outcomes among patients with lung cancer? A national SEER-Medicare analysis. (January 2018) - Khan, Saad A.; Pruitt, Sandi L.; Xuan, Lei; Makris, Una; Gerber, David E.
Highlights: Autoimmune disease’s impact on cancer treatment and outcomes is examined. Healthcare utilization is increased in cancer patients with autoimmune disease. The presence of autoimmune disease doesn't impact lung cancer treatment selection. There is no significant association between autoimmune disease and mortality. Abstract: Background: The advent of cancer immunotherapy has made autoimmune disease in oncology populations clinically important. We analyzed the association of autoimmune disease with treatment and outcomes among lung cancer patients. Methods: Using linked Surveillance Epidemiology and End Results (SEER)-Medicare data, we identified lung cancer patients diagnosed between 1992 and 2009 with autoimmune diseases. We recorded number and timing of autoimmune disease diagnoses, lung cancer treatment, and markers of healthcare utilization including emergency department visits, hospitalizations, and outpatient visits. To account for potential lead-time bias, we used a matched case-control analysis wherein living and deceased patients were matched on survival time. We performed unadjusted and multivariable adjusted logistic regressions separately by cancer stage for all-cause and lung cancer-specific mortality. Results: Among 172, 285 lung cancer patients, 23, 084 (13.4%) had ≥1 autoimmune disease at any time. Overall, 10, 927 patients (6.3%) had one autoimmune disease before cancer diagnosis; 9338 (5.4%) had two or more before cancer diagnosis; and 2819 (1.6%) had one or more after cancer diagnosis. Healthcare utilization was higher in the autoimmune disease population. Lung cancer treatment patterns were similar among patients with and without autoimmune disease and there was no significant association with mortality. Conclusions: Among patients with lung cancer, autoimmune disease does not influence treatment patterns and is not associated with mortality.